2015
DOI: 10.1111/ecc.12312
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics associated with default of treatment and follow-up in patients with cancer

Abstract: Defaulting is an important issue across all medical specialties, but much more so in cancer as delayed or incomplete treatment has been shown to result in worse clinical outcomes such as treatment resistance, disease progression as well as lower survival. Our objective was to identify psychosocial variables and characteristics associated with default among cancer patients. A total of 467 consecutive adult cancer patients attending the oncology clinic at a single academic medical centre completed the Hospital A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…To our knowledge, this is the first study that specifically defined and address surgical adherence. The study has shown a better adherence rate in comparison with the compliance rate in the same center, which was 66.0% . This implies that once patients agreed with surgery, they followed the recommendations.…”
Section: Time To Surgery Interval and Type Of Surgery In Breast Cancesupporting
confidence: 89%
See 1 more Smart Citation
“…To our knowledge, this is the first study that specifically defined and address surgical adherence. The study has shown a better adherence rate in comparison with the compliance rate in the same center, which was 66.0% . This implies that once patients agreed with surgery, they followed the recommendations.…”
Section: Time To Surgery Interval and Type Of Surgery In Breast Cancesupporting
confidence: 89%
“…The study has shown a better adherence rate in comparison with the compliance rate in the same center, which was 66.0%. 6 This implies that once patients agreed with surgery, they followed the recommendations. Delay in the presentation was associated with nonadherence to surgery.…”
mentioning
confidence: 99%
“…Chen et al (2015) found that the delay or refusal of treatment in breast cancer patients was associated with older age, catastrophic illness belief and the severity of comorbidity. Chan, Wan Ahmad, Md Yusof, Ho, and Krupat (2015) noted that of 467 cancer patients, 34.0% (N = 159) reported refusal, delay, or discontinuation of treatment or clinic visits and the major associated factor was psychological distress. Gorphe et al (2016) found that advanced laryngeal cancer patients who refused laryngectomy following an insufficient response to induction chemotherapy did not experience decreased functional and oncological outcomes.…”
Section: Refusing Treatment and Related Factorsmentioning
confidence: 99%
“…() found that the delay or refusal of treatment in breast cancer patients was associated with older age, catastrophic illness belief and the severity of comorbidity. Chan, Wan Ahmad, Md Yusof, Ho, and Krupat () noted that of 467 cancer patients, 34.0% ( N = 159) reported refusal, delay, or discontinuation of treatment or clinic visits and the major associated factor was psychological distress. Gorphe et al.…”
Section: Introductionmentioning
confidence: 99%
“…In our prior work with this cohort, the rate of treatment nonadherence or default (34%) was significant, although it was not linked to rates of psychological distress. 35 Breast cancer appeared to be a protective factor for PTSD at 6-months, but not at 4-years, follow-up. Because breast cancer is a very common malignancy, it is possible that greater societal understanding and the wider availability of support programs tailored for breast cancer (compared with the fewer support programs for patients with other cancer types) initially serve as protective factors against PTSD, but that this protective effect attenuates with distance from the original diagnosis.…”
mentioning
confidence: 92%